Новые находки ящериц и змей на территории Средней Азии - Щербак, Н.Н. (Вестник зоологии, 1979)
The article is an information on findings of Alsophylax loricatus, A. spinicauda, Gymnodactylus fedtschenkoi G.longipes, G. caspius, Eublepharis turcmenicus, Eumeces faeniolatus, E. schneideri, Ablepharus pannonicus (=A. brandti), A. alaicus, Eryx tataricus, Litorhynchus ridgewayi, Oligodon taeniolatus, Psammophis schokari. Some findings specify essentially boundaries of areas of distribution.